Adverse drug reaction profile at psychiatry out-patient department of a tertiary referral centre in Central India - Solanke, Bhupendra; Mahatme, Mohini S.; Dakhale, Ganesh; Hiware, Sachin; Shrivastava, Meena; Waradkar, Pravin (International Journal of Basic & Clinical Pharmacology, 2017)
Modern lifestyle and unfulfilled desires leads to very common diseases of today like anxiety, depression and schizophrenia. Therefore, last one and half decade there has been an exponential rise in the use of psychotropic medication. Antipsychotic polypharmacy is being practiced with increasing frequency. Polypharmacy is one of the leading cause of adverse drug reactions (ADRs) in psychiatric patients. In India, pharmacovigilance activity is still in initial stages and there are only few reports available on incidence of ADRs due to psychopharmacological agents (PPAs). Also, India rates below 1% in terms of ADR reporting against the world’s rate of 5%. Very few studies have described patient characteristics and treatment patterns associated with long-term use of the drugs. This prompted us to do evaluation of adverse drug reactions of PPAs in tertiary referral centre for a longer duration. This study was designed to prospectively monitor and analyze the pattern of occurrence of ADRs to PPAs in OPD of our tertiary care hospital. Our further aim was to make causality and severity analysis of psychopharmacological drug reactions.